More than a game : a history of the African American experience in sport - Wiggins, David Kenneth, 1951- (The African American experience, 2018)
"More than a Game discusses how African American men and women sought to participate in sport and what that participation meant to them, the African American community, and the country. It discusses the varied experiences of African Americans in sport and how their participation has both reflected and changed views of race"--